2012
DOI: 10.1111/j.1530-0277.2012.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphodiesterase‐4 (PDE4) Inhibitor Rolipram Decreases Ethanol Seeking and Consumption in Alcohol‐Preferring Fawn‐Hooded Rats

Abstract: Background Alcohol dependence is a complex psychiatric disorder demanding development of novel pharmacotherapies. Since the cyclic AMP (cAMP) signaling cascade has been implicated in mediating behavioral responses to alcohol, key components in this cascade may serve as potential treatment targets. Phosphodiesterase 4 (PDE4), an enzyme that specifically catalyzes the hydrolysis of cAMP, represents as a key point in regulating intracellular cAMP levels. Thus, it was of interest to determine whether PDE4 was invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 58 publications
10
55
1
Order By: Relevance
“…Rolipram is a selective PDE4 inhibitor thought to represent a novel treatment option for alcoholism due to its effects on the cAMP cascade. A recent preclinical study found that rolipram acutely reduced ethanol self-administration in a dose-dependent fashion and also, after chronic dosing, reduced ethanol preference and consumption (Wen et al, 2012). This is consistent with a previous study showing that acute rolipram administration substantially reduced ethanol consumption and preference in mice (Hu et al, 2011).…”
Section: Rolipramsupporting
confidence: 90%
See 1 more Smart Citation
“…Rolipram is a selective PDE4 inhibitor thought to represent a novel treatment option for alcoholism due to its effects on the cAMP cascade. A recent preclinical study found that rolipram acutely reduced ethanol self-administration in a dose-dependent fashion and also, after chronic dosing, reduced ethanol preference and consumption (Wen et al, 2012). This is consistent with a previous study showing that acute rolipram administration substantially reduced ethanol consumption and preference in mice (Hu et al, 2011).…”
Section: Rolipramsupporting
confidence: 90%
“…It has been hypothesized that GDNF functions to reduce these alcohol-related behaviors in animal models by reversing an alcohol-induced allostatic DA deficiency in the mesolimbic system caused by prolonged excessive alcohol consumption and repeated withdrawal (Barak, Ahmadiantehrani, et al, 2011;Barak, Carnicella, et al, 2011). Furthermore, there is evidence that pharmacological inhibition of phosphodiesterase-4 (PDE4), an enzyme that hydrolyses cyclic adenosine monophosphate (cAMP), decreases alcohol intake in mice (Hu et al, 2011) and rat (Wen et al, 2012) models of alcoholism, as well as reduces neuroinflammation and neuronal death in rats . In addition, a recent study found that another phosphodiesterase, PDE10A, mRNA levels correlated with greater alcohol self-administration during a relapse model and with ethanol preference after acquisition (Logrip & Zorrilla, 2012), suggesting that inhibition of PDE10A may have behavioral effects on alcohol ingestion.…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%
“…Recent studies in rodent models have demonstrated decreased drinking behavior in animals given phosphodiesterase inhibitors (Hu et al, 2011;Wen et al, 2012;Blednov et al, 2014;Franklin et al, 2015). Together, these studies suggest that phosphodiesterase inhibition provides a promising target for the treatment of alcohol use disorders.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, the loss of PKA activation at 4 hours may suggest that restoration of PKA activation could reverse the effect of ethanol at this time point. Recent studies finding a reduction in drinking of rodents coexposed to the phosphodiesterase inhibitor rolipram further underscore the potential therapeutic relevance of manipulating PKA signaling in the treatment of alcohol use disorders (Hu et al, 2011;Wen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%